Prediction of 2020 Mobile Sales Trends Using the Weighted Product Method - Devi Permata Sari Sianturi; Jijon Raphita Sagala (Institute of Computer Science (IOCS), 2020)
Mobile is a communication tool that has the ability like a computer with a variety of functions that is easy to carry anywhere and anytime.The current trend of cellphones is marked by the emergence of increasingly sophisticated types, models and brands with increasingly diverse features such as games, music, cameras, videos and social media. Therefore, nowadays there are many cellphone shops that sell cellphones, in addition to that the development of cellphones has made choosing a cellphone a long and complicated process to produce the best choice that suits your needs. This study aims to produce a decision for the selection of mobile phones using the weighted product method. Weighted product uses the multiplication technique to relate the attribute rating, where the rating of each attribute must be ranked first with the weight of the attribute concerned to produce the largest value that will be selected as the best alternative. The application of the Weighted Product method uses criteria, namely camera (C1), ram (C2), rom (C3), price (C4), weight (C5), and battery (C6). The results of this study indicate that the recommended alternative is A3, namely OPPO type OPPO A9 2020 with a V value of 0.093.